2006
DOI: 10.1029/2005wr004184
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Pacific and Atlantic ocean sea surface temperatures and U.S. streamflow variability

Abstract: An evaluation of Pacific and Atlantic Ocean sea surface temperatures (SSTs) and continental U.S. streamflow was performed to identify coupled regions of SST and continental U.S. streamflow variability. Both SSTs and streamflow displayed temporal variability when applying the singular value decomposition (SVD) statistical method. Initially, an extended temporal evaluation was performed using the entire period of record (i.e., all years from 1951 to 2002). This was followed by an interdecadal‐temporal evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 29 publications
5
84
0
Order By: Relevance
“…Tootle and Piechota, 2006;Barlow et al, 2001;. In the context of this study, however, the pronounced similarity to the equivalent patterns found in precipitation and temperature is a sufficient proof that the space-time patterns of low-frequency runoff follow closely the atmospheric drivers.…”
Section: Space-time Patternssupporting
confidence: 55%
See 3 more Smart Citations
“…Tootle and Piechota, 2006;Barlow et al, 2001;. In the context of this study, however, the pronounced similarity to the equivalent patterns found in precipitation and temperature is a sufficient proof that the space-time patterns of low-frequency runoff follow closely the atmospheric drivers.…”
Section: Space-time Patternssupporting
confidence: 55%
“…Krakauer and Fung, 2008;Small et al, 2006;Tootle and Piechota, 2006] and large scale atmospheric circulation patterns [e.g. Barlow et al, 2001;Rajagopalan et al, 2000;Tootle and Piechota, 2006;Tootle et al, 2005].…”
Section: Principles Of Large-scale Hydrological Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…The data are average monthly values (not anomalies). During the past few decades, a large number of studies have investigated the above streamflow data set (or a part or variant of it) in many different contexts (e.g., Slack and Landwehr, 1992;Kahya and Dracup, 1993;Vogel and Sankarasubramanian, 2000;Sivakumar, 2003;Tootle and Piechota, 2006;Patil and Stieglitz, 2012;Sivakumar and Singh, 2012;Kiang et al, 2013). Some of these studies have explicitly addressed the connections of streamflow between the stations, including in the context of data correlations, catchment similarities, and other measures; see, Patil and Stieglitz (2012) and Kiang et al (2013) for some recent studies.…”
Section: Study Area and Datamentioning
confidence: 99%